2016
DOI: 10.1158/1940-6207.capr-15-0425
|View full text |Cite
|
Sign up to set email alerts
|

Metformin for Reducing Racial/Ethnic Difference in Prostate Cancer Incidence for Men with Type II Diabetes

Abstract: Racial/ethnic disparity in prostate cancer (PCa) is under studied in men with diabetes who are at higher risk for aggressive PCa. This study assessed the race/ethnic disparity in PCa incidence for men with type 2 diabetes (T2D), and whether the impact of metformin on PCa incidence varied by race/ethnicity. We conducted a retrospective study in 76,733 male veterans with T2D during 2003–2012. Cox proportional hazard model adjusting for covariates and propensity scores of metformin use and race/ethnic group membe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…In the primary analysis, metformin use was defined as ≥180 days of prescription at any dose, an exposure cut‐point commonly used in clinical research . Non metformin users were those without any prescription for metformin during the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the primary analysis, metformin use was defined as ≥180 days of prescription at any dose, an exposure cut‐point commonly used in clinical research . Non metformin users were those without any prescription for metformin during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Predictors in the analysis of HCC incidence included indicators of NHAA and Hispanics (NHW being the referent), study duration, age, comorbidity, indicators of statin use and beta‐blocker use, change in LDL, HbA1c, and BMI, alcohol‐related mental health disorders, abnormal liver functions, and neighborhood SES. To infer the racial/ethnic disparity in HCC incidence that is in concordance with the NAM's definition, the inverse propensity scores of race/ethnicity were incorporated as the weights in the logistic regression model to calibrate between race/ethnic groups. The predictors for propensity scores of race/ethnicity group membership included baseline age, neighborhood SES, HbA1c, BMI, LDL, statin use, beta‐blocker use, and Charlson comorbidity score.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that among diabetic men without metformin use, prostate cancer incidence was higher in Hispanics and African Americans than in non-Hispanic Whites. 224 Use of metformin alone or metformin plus statins was associated with a greater reduction in prostate cancer incidence in Hispanics compared with non-Hispanic Whites, but not between African Americans and non-Hispanic Whites. Similarly, there are interethnic differences in the frequencies of functional alleles of hERG 225 and CYP2J2, 226 which could impact the results of studies investigating the efficacy of astemizole as an anticancer agent.…”
mentioning
confidence: 87%
“…Heath et al have recently reported significant differences and trends in molecular signatures of the three cancer types in African Americans and Caucasians, a finding that implies racial/ethnic differences in carcinogenesis and response to the drug being investigated. It has been reported that among diabetic men without metformin use, prostate cancer incidence was higher in Hispanics and African Americans than in non‐Hispanic Whites . Use of metformin alone or metformin plus statins was associated with a greater reduction in prostate cancer incidence in Hispanics compared with non‐Hispanic Whites, but not between African Americans and non‐Hispanic Whites.…”
Section: Challenges and Overcoming Obstaclesmentioning
confidence: 99%
“…In this issue, C-P Wang et al studied the effect of metformin on prostate cancer incidence in the Veterans Administration Health Care System (1). According to their analyses, metformin had a protective effect on prostate cancer risk in the Hispanic Americans but not in Non-Hispanic White Americans, African Americans, or Asian Americans.…”
mentioning
confidence: 99%